Software quality: predicting reliability of a software using decision tree - Shakiru, Ayanloye O.; Yusuf, Mahmud Ahmad; Koh, Tieng Wei; Letchmunan, Sukumar (Asian Network for Scientific Information, 2014)
System availability can be expressed as an attribute of reliability that determines the total time a system or component is functioning. Most available models try to predict availability of a software during its life cycle but there are very few or no models that predict a software going days without a failure. Over the years, decision tree model have been used as a reliable technique for prediction. In this study, based on the sample data collected by John Musa of Bell Telephone Laboratories, a decision tree model has been used to predict the availability of a system going days without a failure. This study concluded that a decision tree model is able to decide availability of a software in terms of going days without a failure.